1st-person deontic verbs: a general corpus versus a parliamentary corpus NO 1st-person deontic verbs: a general corpus versus a parliamenary corpus - De Cock, Barbara (Círculo de Lingüística Aplicada a la Comunicación, 2014)
In this article, we present the results of an analysis of verbs expressing deonticity in Spanish, focussing on their use on the 1st person, which has received little attention in the literature so far. By means of an analysis in terms of ‘modal source’ and ‘modal agent’ (Verstraete 2005), we will analyze the conceptualization of the relationship between the speaker and his surroundings. The corpus analysis will shows that the use of deontic verbs which are considered prototypical are in fact not very frequent and that it is necessary to take into account the (partial) overlap of modal source and agent in 1st person forms. Those results are compared with the use of deontic verbs as a rhetorical strategy in parliamentary debate. The absence of some deontic verbs is explained by the desire to avoid a conceptualization which would be too authoritarian, namely that of the speaker as mere modal source. Moreover, the metadiscursive nature of parliamentary debate influences the use of deontic verbs.
Keywords: deonticity; discourse; parliamentary debate; modality.